2017
DOI: 10.1002/2327-6924.12475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of common barriers to rural patients utilizing hospice and palliative care services

Abstract: Background and purpose The aim of this literature review is to explore barriers and potential solutions related to hospice (HC) and palliative care (PC) services among rural residents. Although the healthcare system is continually advancing, healthcare providers may not be optimizing HC and PC referrals for the growing rural population who underutilize these services. Suggested methods to close the utilization gap between HC and PC services among rural patients appear feasible, but universal effectiveness cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
2
27
0
3
Order By: Relevance
“…18 Some additional barriers to accessing palliative care in rural areas also included lower socioeconomic status, a misunderstanding of what palliative care treatment is, and health care providers feeling ill-equipped to manage the care needs of patients nearing their end of life. 10 Moreover, the barriers that exist to access palliative care are not exclusive to rural Canada. 10,19,20 A published literature review that included palliative care research studies from Australia, USA, Canada, and Europe indicated that barriers to access palliative care are all inclusive with the main distinguishing criteria being rurality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Some additional barriers to accessing palliative care in rural areas also included lower socioeconomic status, a misunderstanding of what palliative care treatment is, and health care providers feeling ill-equipped to manage the care needs of patients nearing their end of life. 10 Moreover, the barriers that exist to access palliative care are not exclusive to rural Canada. 10,19,20 A published literature review that included palliative care research studies from Australia, USA, Canada, and Europe indicated that barriers to access palliative care are all inclusive with the main distinguishing criteria being rurality.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many challenges exist for providing palliative care in a rural Canadian setting both for health care delivery and at the level of the palliative care recipient. 10 Previously published research references inequity issues of access to resources, lengthy travel to urban centers to obtain palliative services, as well as a lack of available health care professionals and health care resources. [11][12][13][14][15][16][17] Furthermore, many rural residents often wish to receive care in their community with their families to avoid travel-related issues and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, the majority of the findings of this review remain consistent with the findings of prior reviews where authors also reported an inverse relationship between EOL resource use and age and a consistent trend of underutilisation of palliative services among rural EOL cancer decedents [ 41 ]. Past reviews that focussed on healthcare provider and patient barriers and quality of EOL care also identified low provider comfort, limited scope of practice [ 42 ] as well as family member’s avoidance issues around dying [ 43 ] as being distinct challenges faced by rural communities when it comes to EOL cancer care. From an ecological perspective, this systematic review remains the first to provide additional insight into the influence geographical remoteness has on the patterns of EOL cancer care among patient populations residing in rural and urban locations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study focused on a very particular U.S. rural culture, and hence, some of our results may not be transferable to other global rural populations. While recent reviews have highlighted the increasing role and potential of lay workers bringing palliative care to rural communities globally, 55,56 we recommend that programs in other countries and rural settings gain stakeholder feedback from their own populations before testing or implementing similar programs.…”
Section: Discussionmentioning
confidence: 99%